Complete Transection of the Cystic Duct and Artery after Blunt Trauma: A Case Report - Sung Hoon Cho; Kyoung Hoon Lim (Journal of Trauma and Injury)
Extrahepatic biliary tract and gallbladder injuries following blunt abdominal trauma are uncommon. Traumatic cystic duct transection is even rarer, which has frequently caused missed diagnosis and delayed treatment. An 18-year-old female patient with no past medical history was transferred to the Trauma Center of Kyungpook National University Hospital after falling from a height of approximately 20 meters. She became hemodynamically stable after initial resuscitation, and initial contrast-enhanced abdominal computed tomography (CT) showed right kidney traumatic infarction and multiple intrahepatic contusions with minimal fluid collection but no extravasation of the contrast. She was admitted to the intensive care unit. On the second day of hospitalization, her abdomen became distended, with follow-up CT showing a large collection of intra-abdominal fluid. Laparoscopic exploration was then performed, which revealed devascularization of the gallbladder with complete transection of the cystic duct and artery. Laparoscopic cholecystectomy was performed, as well as primary closure of the cystic duct orifice on the common bile duct using a 4-0 Prolene suture. After surgery, no clinical evidence of biliary leakage or common bile duct stricture was observed.